Investigating the cellular antioxidant and anti-inflammatory effects of the novel peptides in lingzhi mushrooms. Issue 10 (October 2022) - Aursuwanna, Thanyaporn; Noitang, Sajee; Sangtanoo, Papassara; Srimongkol, Piroonporn; Saisavoey, Tanatorn; Puthong, Songchan; Reamtong, Onrapak; Karnchanatat, Aphichart
Abstract: The lingzhi mushroom ( Ganoderma lucidum ) is well known for its medicinal properties and has long played a role in traditional oriental medicine due to its health-giving benefits and potential to extend life expectancy. The mushroom contains a number of highly bioactive compounds and can also act as an excellent source of protein. This research investigated the peptides obtained from the protein hydrolysates of lingzhi mushrooms to assess their free radical scavenging abilities. These peptides were acquired via different proteases (Alcalase, Neutrase, papain, and pepsin-pancreatin) and were tested at a range of different concentrations (1.0%, 2.5%, and 5.0% w/v). The highest levels of 2, 2′-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS), 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and nitric oxide (NO) radical scavenging activities were presented by lingzhi mushroom hydrolysate using 2.5% (w/v) pepsin-pancreatin after 6 h of digestion. The hydrolysate was then fractionated using 10, 5, 3, and 0.65 kDa molecular weight cut-off membranes. The results showed that the MW 0.65 kDa fraction had the highest level of free radical scavenging activity. Further analysis of this MW 0.65 kDa fraction began with another RP-HPLC fractionation technique to obtain three further sub-fractions. De novo peptide sequencing using electrospray ionization quadrupole time-of-flight mass spectrometry (ESI-Q-TOF-MS/MS) was chosen as the optimum method for studying the F3 sub-fraction. DRVSIYGWG and ALLSISSF were discovered as new peptides with different antioxidant properties. Adenocarcinoma colon (Caco-2) cells showed the antioxidant action of these synthesized peptides. This activity was linked to peptide concentration. The peptides and their pure synthetic counterparts were found to reduce NO generation by RAW 264.7 macrophages without causing cytotoxicity. The results of gene expression reveal that the DRVSIYGWG and ALLSISSF peptides were able to cut the expression of the proinflammatory cytokine genes iNOS, IL-6, TNF-α, and COX-2 in the context of RAW 264.7 macrophages. Graphical abstract: Image 1 Abstract : Lingzhi mushroom; Peptides; Antioxidant; Anti-Inflammatory.